Peeking Inside Pandora's Box: One University's Journey into the Redesign of Teacher Educator Preparation - Frank O'Neil Dykes; Brenda K. Gilliam; Joanna Neel; Kathleen Everling (Arizona State University, 2012)
In the last two decades, there have been various calls for reform in teacher education programs to address the needs of students from culturally and linguistically diverse backgrounds and students with disabilities.  Consequently, many teacher education preparation programs are reviewing and redesigning their programs to meet the needs of the teacher of the 21st century. This manuscript will describe the development and implementation of a new certification program that integrates preservice teacher preparation, Special Education and English as a second language into a 123 hour degree program.